JUMLAH BUNGA DAN POLONG EMPAT KULTIVAR LOKAL KACANG TANAH ASAL BANTEN (Arachis hypogaea L.) PADA KETERSEDIAAN AIR TANAH YANG MENURUN SELAMA FASE REPRODUKTIF - Rusmana . (Jurnal Agroekoteknologi, 2016)
Experiments were performed to characterize the response of peanut local cultivars from Banten to soil water availability decreased during the reproductive phase. The experiments used factorial randomized block design with three replications of two factors. The first factor was the soil water availability consists of three levels (100%, 75%, and 50%). The second factor was the peanut local cultivars from Banten consists of four levels (local cultivars of Cikeusal, Petir, Anyer, and Cisoka).  The results showed a similar general pattern that was the decreasing soil water availability resulting in the decreasing amount of flowers and pod number of peanut local cultivars from Banten.  Flowers appear began to plant at 24 and ending at 46 days after planting with a period of at most appear at the age of 26 up to 36 DAP.  Four peanut local cultivars from Banten showed no difference in tolerance to the declining of soil water availability.  Number of flowers and peanut pods begin to decrease when soil water availability as as much as 75%. Keywords: Flower, Local cultivars, Peanuts, Soil water availability, Pod number